DEMOCRACY AND THE RULE OF LAW IN SUB-SAHARAN AFRICA - Tal, Mohammed Kwarah (IJRDO - Journal of Social Science and Humanities Research, 2019)
The contradictions of the colonial economy instigated African nationalists to interrogate the basis for colonialism and demanded for the decolonization of the colonies. These efforts led to the formal independence of many African countries in the 1960s and beyond. As the retreating colonial powers left behind myriads of economic, political and social problems that the comprador bourgeoisie who took over the reins of power could hardly surmount, most of these countries became easy preys to some adventurous and power hungry military elements who, in quick succession, overthrew the civilian administrations put in place. Until the late 1980s through the 1990s when the clamour for democracy and the rule of law took center stage in many Sub-Saharan African states, authoritarianism held sway. This paper explored and evaluated the relationship between “democracy” and the “rule of law” in Sub-Saharan Africa. An overview of the political economy of the region presents a grim picture of economic and political crises manifested, among others, by massive poverty, wars, corruption, and erosion of democratic values and the rule of law. The theory of African Democracy was adopted as the theoretical framework, while secondary data/library research through qualitative method was employed. In conclusion, the Paper submits that democracy and the rule of law remain a sham, a Trojan horse, for the majority of the people, except, perhaps for the elite oligarchs that dominate the economic and political structures of the Sub-region. Suggestions have been put forward for the proper practice of democracy and observance of the rule of law in Sub-Saharan Africa.